MOTIVASI BELAJAR MAHASISWA IKIP BUDI UTOMO DALAM PEMBELAJARAN BLENDED LEARNING PADA MATAKULIAH ILMU GIZI - Hartati, Tri Asih Wahyu; Lestari, Purwaning Budi; Pangestuti, Ardian Anjar (Universitas Islam Balitar, 2020)
Classroom action research is conducted to determine the application of blended learning in Nutrition Science at IKIP Budi Utomo and increase student motivation through blended learning. The research method uses Classroom Action Research for two cycles. Learning motivation is measured using a learning motivation questionnaire at the end of each cycle and the application of blended learning is described based on the lesson plan implementation sheet and the learning observation sheet. The results of this study indicate that IKIP Budi Utomo’s student motivation has increased by 25%. In addition the implementation of blended learning has a positive impact on student skills using technology.